The experimental research on the random variability in the local strength of the selected aluminum alloys - Ferenc, Justyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
This paper presents the results of the experimental research on mechanical properties of selected aluminum alloys, representative of the heat treated alloys (6xxx series) and the strengthened one from cold working only alloys (5xxx series). Results of laboratory tests, which describe the local changes of the strength characteristics of Re, Rm and Young’s modulus E, indicate that variability in the local characteristics of the bars are oscillations around the average values along the axis of the bars. A mathematical model for describing this type of variation is random noise, or random fluctuations around a central value.